Measurement of dynamic magnetization induced by a pulsed field: Proposal for a new rock magnetism method - Kodama, Kazuto (Frontiers in Earth Science, 2015)
This study proposes a new method for measuring transient magnetization of natural samples induced by a pulsed field with duration of 11 ms using a pulse magnetizer. An experimental system was constructed, consisting of a pair of differential sensing coils connected with a high-speed digital oscilloscope for data acquisition. The data were transferred to a computer to obtain an initial magnetization curve and a descending branch of a hysteresis loop in a rapidly changing positive field. This system was tested with synthetic samples (permalloy ribbon, aluminum plate, and nickel powder) as well as two volcanic rock samples. Results from the synthetic samples showed considerable differences from those measured by a quasi-static method using a vibrating sample magnetometer (VSM). These differences were principally due to the time-dependent magnetic properties or to electromagnetic effects, such as magnetic viscosity, eddy current loss, or magnetic relaxation. Results from the natural samples showed that the transient magnetization–field curves were largely comparable to the corresponding portions of the hysteresis loops. However, the relative magnetization (scaled to the saturation magnetization) at the end of a pulse was greater than that measured by a VSM. This discrepancy, together with the occurrence of rapid exponential decay after a pulse, indicates magnetic relaxations that could be interpreted in terms of domain wall displacement. These results suggest that with further developments, the proposed technique can become a useful tool for characterizing magnetic particles contained in a variety of natural materials.